Consumer search and optimal information. (3rd May 2022) - Dogan, Mustafa; Hu, Ju
Abstract: This article studies an information design problem in a sequential consumer search environment. Consumers, whose valuation of firms' products is uncertain, observe a noisy signal about the valuation upon being matched with a firm. The goal is to characterize those signal structures that maximize consumer surplus. We show that the consumer‐optimal signal structure can be found within the class of conditional unit‐elastic demand signal distributions. A rich set of properties and comparative statics of the consumer‐optimal signal distributions are also derived.